PIC simulation of nonlinear regime wake field excitation in cylindrical resonator - Markov, P.I.; Onishchenko, I.N.; Korzh, A.F.; Sotnikov, G.V. (Вопросы атомной науки и техники, 2006)
The nonlinear mechanism of saturation of wake field amplitude, exited in the cylindrical resonator partially filled with dielectric by relativistic train of electron bunches numerically simulated by means of a specially elaborated 2.5- dimensional electromagnetic PIC-code.